Role of the extent of prophylactic regional lymph node radiotherapy on survival in high‐risk neuroblastoma: A report from the COG A3973 study. Issue 7 (9th April 2019) - Braunstein, Steve E.; London, Wendy B.; Kreissman, Susan G.; Villablanca, Judith G.; Davidoff, Andrew M.; DeSantes, Kenneth; Castleberry, Robert P.; Murray, Kevin; Diller, Lisa; Matthay, Katherine; Cohn, Susan L.; Shulkin, Barry; et al.
Abstract: Purpose: Neuroblastoma is the most common extracranial solid pediatric malignancy, with poor outcomes in high‐risk disease. Standard treatment approaches employ an increasing array of aggressive multimodal therapies, of which local control with surgery and radiotherapy remains a backbone; however, the benefit of broad regional nodal irradiation remains controversial. We analyzed centrally reviewed radiation therapy data from patients enrolled on COG A3973 to evaluate the impact of primary site irradiation and the extent of regional nodal coverage stratified by extent of surgical resection. Methods: Three hundred thirty high‐risk neuroblastoma patients with centrally reviewed radiotherapy plans were analyzed. Outcome was evaluated by the extent of nodal irradiation. For the 171 patients who also underwent surgery (centrally reviewed), outcome was likewise analyzed according to the extent of resection. Overall survival (OS), event‐free survival (EFS), and cumulative incidence of local progression (CILP) were examined by Kaplan–Meier, log‐rank test (EFS, OS), and Grey test (CILP). Results: The five‐year CILP, EFS, and OS for all 330 patients receiving radiotherapy on A3973 were 8.5% ± 1.5%, 47.2% ± 3.0%, and 59.7% ± 3.0%, respectively. There were no significant differences in outcomes based on the extent of lymph node irradiation regardless of the degree of surgical resection (< 90% or ≥90%). Conclusion: Although local control remains a significant component of treatment of high‐risk neuroblastoma, our results suggest there is no benefit of extensive lymph node irradiation, irrespective of the extent of surgical resection preceding stem cell transplant.